Collagen diseases as a cause of constrictive pericarditis. - Cooper, D K (1978)
Seven patients with constrictive pericarditis associated with collagen disease underwent pericardiectomy with good results in all but one. The collagen disease was confirmed as rheumatoid arthritis in five patients, but in two its nature remained obscure. In one case the illness was marked by a persistent eosinophilia and eosinophilic infiltration of the pericardium. The association of constrictive pericarditis with rheumatoid arthritis and other collagenoses is briefly discussed.